The Role of KRAS Mutational Analysis to Determine the Site of Origin of Metastatic Carcinoma to the Lung: A Case Report - Ahmed N. Alkhasawneh; Hui-Jia Dong; Chen Liu; Carmen Allegra; Robert W. Allan (Hindawi Limited, 2012)
Metastatic carcinomas involving the lung are a common specimen encountered in surgical pathology. These metastases may have different morphologic, and architectural patterns and may mimic primary pulmonary adenocarcinoma, especially the intra-alveolar (lepidic) pattern of spread which may simulate a primary pulmonary bronchioloalveolar carcinoma (adenocarcinoma in situ). We present the case of a metastatic pancreatic adenocarcinoma that morphologically mimicked bronchioloalveolar carcinoma of the lung in that the tumor had an exclusive intra-alveolar pattern of spread and had an immunophenotype that was noninformative as to the site of origin (cytokeratin 7+, cytokeratin 20−, TTF-1−). In this case, we used KRAS gene mutation analysis to support that the lung carcinoma represented a metastatic pancreatic carcinoma as they both possessed identical codon 12 KRAS mutations. We show that this method may be a useful way to prove site of origin of metastatic carcinoma-particularly if standard morphologic or immunohistochemical analysis is not definitive.